KNOWLEDGE AS INVESTMENT IN HUMAN RESOURCES TO INCREASE THE COMPANY SUCCESS - NEGULESCU, Oriana Helena (Annals of Spiru Haret University. Economic Series, 2016)
In this era, characterized by rapid changes in information and communication technologies and the increasing competition on the global market, the main factor of strategic development of the modern successful company is the development of strategic resources. The most important strategic resource is the people’s expertise that is bringing competitive advantage to the company. The employees’ knowledge accumulation is probably the main tool the management has to consider in designing strategies for company’s growth. However, the employees’ knowledge is contributing to the knowledge based company, as a factor of success. This paper is aiming to emphasize the main concepts regarding the knowledge based company, the profile of a knowledge based company, the importance of employees’ knowledge accumulation for the company’s development and to consider the knowledge as being an investment by training. The return of investment in human resources knowledge is finally analyzed.